Molecular Insights into Rab7‐Mediated Endosomal Recruitment of Core Retromer: Deciphering the Role of Vps26 and Vps35. (1st December 2014) - Priya, Amulya; Kalaidzidis, Inna V; Kalaidzidis, Yannis; Lambright, David; Datta, Sunando
<x xml:space="preserve">Abstract</x> Retromer, a peripheral membrane protein complex, plays an instrumental role in host of cellular processes by its ability to recycle receptors from endosomes to the trans‐Golgi network. It consists of two distinct sub‐complexes, a membrane recognizing, sorting nexins (SNX) complex and a cargo recognition, vacuolar protein sorting (Vps) complex. Small GTPase, Rab7 is known to recruit retromer on endosomal membrane via interactions with the Vps sub‐complex. The molecular mechanism underlying the recruitment process including the role of individual Vps proteins is yet to be deciphered. In this study, we developed a FRET‐based assay in HeLa cells that demonstrated the interaction of Rab7 with Vps35 and Vps26 in vivo. Furthermore, we showed that Rab7 recruits retromer to late endosomes via direct interactions with N‐terminal conserved regions in Vps35. However, the single point mutation, which disrupts the interaction between Vps35 and Vps26, perturbed the Rab7‐mediated recruitment of retromer in HeLa cells. Using biophysical measurements, we demonstrate that the association of Vps26 with Vps35 resulted in high affinity binding between the Vps sub‐complex and the activated Rab7 suggesting for a possible allosteric role of Vps26. Thus, this study provides molecular insights into the essential role of Vps26 and Vps35 in Rab7‐mediated recruitment of the core retromer complex. <inline-graphic xlink:href="ark:/27927/pgh2xqjqfw9" mimetype="image" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />